ENHANCING HUMAN RESOURCE MANAGEMENT EFFICIENCY IN MANUFACTURING INDUSTRIES BASED ON MODERN MANAGERIAL APPROACHES (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the issue of enhancing human resource management efficiency in manufacturing industries based on modern managerial approaches. The relevance of the topic is determined by the growing need for industrial enterprises to improve labor productivity, strengthen workforce adaptability, and ensure sustainable development under conditions of technological change, market competition, and organizational modernization. In the manufacturing sector, human resources represent not only a labor factor, but also a strategic asset that directly influences production stability, product quality, innovation capacity, and the long-term competitiveness of enterprises. For this reason, the modernization of human resource management has become one of the central directions of industrial management improvement.The study is based on the assumption that traditional personnel management models are no longer sufficient for manufacturing industries that operate in a dynamic environment requiring flexibility, efficiency, and continuous professional development. Special attention is given to modern managerial approaches such as competency-based management, performance-oriented evaluation, motivation systems, workforce planning, digital HR tools, and the integration of strategic and operational personnel decisions. The article substantiates that the efficiency of human resource management in manufacturing industries depends on the extent to which enterprises are able to combine organizational goals with employee development, labor discipline, professional training, and effective managerial coordination.The research shows that the application of modern managerial approaches contributes to improving the quality of personnel decisions, optimizing labor organization, increasing employee engagement, and strengthening the overall effectiveness of production management. As a result, the article proposes conceptual directions for enhancing human resource management efficiency in manufacturing industries, aimed at ensuring higher productivity, stronger organizational resilience, and more sustainable industrial growth.